2022
DOI: 10.1093/mnras/stac980
|View full text |Cite
|
Sign up to set email alerts
|

Stellar and black hole assembly inz< 0.3 infrared-luminous mergers: intermittent starbursts versus super-Eddington accretion

Abstract: We study stellar and black hole mass assembly in a sample of 42 infrared-luminous galaxy mergers at z < 0.3 by combining results from radiative transfer modelling with archival measures of molecular gas and black hole mass. The ratios of stellar mass, molecular gas mass, and black hole mass to each other are consistent with those of massive gas-rich galaxies at z < 0.3. The advanced mergers may show increased black hole mass to stellar mass ratios, consistent with the transition from AGN to ellip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 151 publications
2
24
0
Order By: Relevance
“…A "major" merger with a gas-rich galaxy might suffice, if the encounter parameters strongly favored dissipation of angular momentum in the molecular gas so it could funnel to the nucleus. This is in some senses plausible: it has recently been shown that gas-rich major mergers can lead to the central SMBH growing by ∼1 dex, with the stellar mass increasing more modestly (Farrah et al 2022). Such an event would, however, lead to rapid gas accretion in a relatively short burst, resulting in an AGN.…”
Section: Preferential Conversion Of Molecular Gas Mass To Supermassiv...mentioning
confidence: 99%
“…A "major" merger with a gas-rich galaxy might suffice, if the encounter parameters strongly favored dissipation of angular momentum in the molecular gas so it could funnel to the nucleus. This is in some senses plausible: it has recently been shown that gas-rich major mergers can lead to the central SMBH growing by ∼1 dex, with the stellar mass increasing more modestly (Farrah et al 2022). Such an event would, however, lead to rapid gas accretion in a relatively short burst, resulting in an AGN.…”
Section: Preferential Conversion Of Molecular Gas Mass To Supermassiv...mentioning
confidence: 99%
“…A very recent radiative hydrodynamical simulation [13] found the super-Eddington phase as early stages when the bulge forms and the black hole seed is fed by a massive gaseous disk. The super-Eddington accretion phase was also recently detected in 12 objects within a sample of 42 infrared-luminous galaxy mergers where the super-Eddington accretion is claimed to be an important channel for the black hole growth in infrared-luminous galaxies at all redshifts [14]. In general, super-Eddington sources populate the extreme right tail of the Quasar Main Sequence in the optical plane showing the highest ratio of the Fe II pseudo-continuum to Hβ equivalent width and the narrowest emission lines [4,15], and the 26 sources selected as extreme in this plane show the mean Eddington ratio of 21 [16].…”
Section: Introductionmentioning
confidence: 77%
“…IC 860's SMBH is predicted to be under massive, where the total enclosed mass of gas, dust, stars, and the SMBH is of order of the SMBH mass predicted by the M SMBH − σ relationship (M SMBH ∼ 10 7 M ; Aalto et al 2019;McConnell & Ma 2013;Davis et al 2019). Less massive SMBHs also more commonly accrete at super-Eddington levels (Shirakata et al 2019;Farrah et al 2022). Furthermore, IC 860's Paα luminosity is under luminous for normal star formation (Alonso-Herrero et al 2006).…”
Section: Abundances Of Methanimine In Ic 860 and Milky Way Environmentsmentioning
confidence: 99%